Developing and evaluating a patient decision aid for hormone therapy to manage symptoms of surgical menopause: the story behind the "SheEmpowers" patient decision aid. Issue 2 (February 2021) - Siyam, Tasneem; Shivji, Alisha; Ross, Sue; Eurich, Dean T.; Lavasanifar, Afsaneh; Yuksel, Nesé
Abstract: Objectives: To develop and evaluate an evidence-based patient decision aid (PDA) that can support women making decisions on hormone therapy (HT) for the management of early surgical menopause. Methods: The PDA development was guided by the Ottawa Decision Support Framework and the International Patient Decision Aid Standards and involved three phases: an exploratory phase to identify women's decisional needs; a development phase to identify evidence related to treatment options and draft initial prototype; and an evaluation phase to evaluate the prototype and elicit views on acceptability in women ( N  = 12). All phases were driven by a multidisciplinary group of researchers, clinicians, and patient stakeholders to ensure women's priorities were met. Results: A prototype PDA was drafted based on needs identified from the exploratory phase. The PDA has five domains: information on surgical menopause and HT; HT outcome probabilities; patient stories; values clarification; and guidance in deliberation. Participants in the evaluation phase perceived the tool as acceptable and offered suggestions for modifications. Conclusion: Through our adopted, systematic approach the SheEmpowers PDA was developed to help women overcome deterrents to decision-making related to lack of knowledge, decision-making skills, and involvement in therapy decisions. The decisional effectiveness of the tool is to be assessed in future studies. Abstract : Supplemental Digital Content is available in the text